Update on the Biological and Clinical Relevance of Mast Cells in Chronic Rhinosinusitis with Nasal Polyps - Luca Giovanni Locatello; Silvia Tonon; Vincenzo Mele; Simone Santini; Cesare Miani; Carlo Ennio Michele Pucillo (Biomedicines)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a common inflammatory disorder whose complex immunopathogenesis has yet to be fully elucidated. Endotype-2 CRSwNP is the most common form of disease where eosinophils are the main drivers of inflammation. Traditional treatments for CRSwNP have centered around intranasal or systemic corticosteroids and endoscopic sinus surgery (ESS). However, recent advancements in targeted therapies have introduced novel biological agents that specifically target key inflammatory mediators such as IL-4, IL-5, and IL-13. These biologics offer promising options for patients with CRSwNP, particularly those who do not respond adequately to conventional treatments. Nonetheless, some patients do not satisfactorily respond to these drugs because of an insufficient blockade of the inflammatory process. The mast cell (MC) is another important (and somehow neglected) actor in the pathogenesis of CRSwNP, and the latest clinical and translational evidence in this field has been reviewed in the present paper.